2020
DOI: 10.12965/jer.2040650.325
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between movement dysfunctions and sports injuries according to gender of youth soccer player

Abstract: The purpose of this study is to investigate relationship between movement dysfunctions and sports injuries according to gender of youth soccer player. Thirty-eight middle school soccer players participated in this study and they were divided into male (n= 19) and female (n= 19) groups. The Functional Movement Screen (FMS) and the Quadricepsangle (Q-angle) during single-leg squat were analyzed for identifying imbalance and asymmetry of the body, and sports injury questionnaire was examined for 6 months after FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Of the available studies, some include both boys and girls [32,40,41,44 Of the studies that included both boys and girls, some studies have not reported sex differences in the FMS [57,77,78,82]. Other studies have reported no significant differences in the FMS scores between boys and girls [36,38,41,44,48,49,58,62,63,76,81,83,86,87,[89][90][91]93,99,103,110]. Fewer studies have reported that girls perform better than boys [32,40,45,54,55,59,88,108] and even fewer studies report that boys perform better than girls [107,111].…”
Section: Sex and Age Differences In The Performance On The Fmsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the available studies, some include both boys and girls [32,40,41,44 Of the studies that included both boys and girls, some studies have not reported sex differences in the FMS [57,77,78,82]. Other studies have reported no significant differences in the FMS scores between boys and girls [36,38,41,44,48,49,58,62,63,76,81,83,86,87,[89][90][91]93,99,103,110]. Fewer studies have reported that girls perform better than boys [32,40,45,54,55,59,88,108] and even fewer studies report that boys perform better than girls [107,111].…”
Section: Sex and Age Differences In The Performance On The Fmsmentioning
confidence: 99%
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 3 more Smart Citations